Chimes at midnight [videorecording (DVD)] - Welles, Orson, 1915-1985; Welles, Orson, 1915-1985; Welles, Orson, 1915-1985; Baxter, Keith, 1933-; Moreau, Jeanne, 1928-2017; Gielgud, John, 1904-2000; Shakespeare, William, 1564-1616; Holinshed, Raphael, approximately 1525-1580? (Criterion collection, 2016)
Prince Hal must choose between loyalty to Sir John Falstaff or to his father, King Henry IV.